MORAL EDUCATION FOR CHILDREN WITH SPECIAL NEEDS THROUGH THE HABITUATION OF RELIGIOUS ACTIVITIES - Abror, Muhammad Farisi (JPI (Jurnal Pendidikan Inklusi), 2018)
Children with special needs require assistance to protect and optimize growth. All the elements of child development in children with special needs to be optimized, including the development of norms and religion so that it can develop well. The development optimization can do practice in the family, schools, and communities by carrying out religious activities habituation.